Preserving the monarchy : the comte de Vergennes, 1774-1787 - Price, Munro (Cambridge ; New York : Cambridge University Press, 1995)
The comte de Vergennes is best known as one of the great foreign ministers of modern French history, but for much of the 1780s he was also first minister in all but name. This 1995 book was the first to deal in depth with the critical part he played in French domestic policies on the eve of the Revolution. It studies Vergennes' role in the context of the debate on the nature and future of the French monarchy in the two decades before the Revolution. His financial reforms, fully examined here, were the last attempt to restructure the monarchy in accordance with its traditional principles. The failure of this undertaking accelerated the final collapse of the royal government. Preserving the Monarchy is based on archival research, as well as reinterpretations of the established sources. The result is a significant study, not merely of Vergennes but of the end of the ancien régime.
1. Recalled to life -- 2. The question of reform: Turgot, Necker, and Vergennes -- 3. Vergennes as first minister: the comite des finances -- 4. The fall of the comite des finances -- 5. The politics of judicial reform -- 6. The politics of retrenchment, 1783-1785 -- 7. The ministry, its divisions, and the parlement of Paris, 1785-1786 -- 8. The Dutch imbroglio -- 9. Death and posterity.
Includes bibliographical references (pages 242-249) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Vergennes, Charles Gravier, -- comte de, -- 1719-1787.; Vergennes, Charles Gravier, -- comte de, -- 1719-1787; France -- Foreign relations -- 1774-1793.; France -- Politics and government -- 1774-1793.; Finance, Public -- France -- History -- To 1789.; Foreign ministers -- France -- Biography; Diplomats -- France -- Biography; France -- Relations extérieures -- 1774-1793.; France -- Politique et gouvernement -- 1774-1793.; Finances publiques -- France -- Histoire -- Jusqu'à 1789.; Ministres des affaires étrangères -- France -- Biographies; Diplomates -- France -- Biographies; HISTORY; BIOGRAPHY & AUTOBIOGRAPHY -- Historical; Diplomatic relations; Diplomats; Finance, Public; Foreign ministers; Politics and government; France; Monarchie; Binnenlandse politiek; Openbare financiën.; Frankrijk; To 1793; Electronic books; Biographies; History; Biografieën (vorm); Biographies; Biographies